Effect of dissolved hydrogen on removal of double oxide film defects from Al melt. (December 2014) - Chegini, S.; Raiszadeh, R.
Abstract : Effect of increasing the hydrogen content of the melt on the removal of double oxide (bifilm) defects in commercial purity Al melt was investigated using Weibull statistical analysis of mechanical properties of solidified castings and a semiempirical mathematical model that had been developed previously. The results of the Weibull analysis revealed that increasing the H content of the melt from 0·2 to 0·4 mL/100 g and holding the melt in furnace for 30 min caused the Weibull modulus of the casting to increase by ∼73%. Studies (SEM and EDX) of fracture surfaces of the test bars indicated that the number of oxide defects in the melt decreased due to this treatment. The mathematical model suggested that increasing the H content of the melt to ∼0·8 mL/100 g would force all the oxide defects to expand rapidly and float out of the liquid metal in a very short time.